Prospects of Christian Dialogue with other Religions - Pushparajan, A (Journal of Dharma, 1983)
The prospects of Christian dialogue with other religions depends upon finding a proper solution to the various problems encountered and likely to be encountered in the future. These problems are many and varied. A detailed analysis of these problems and their solutions is not the principal aim of this article. For, in my opinion, there is one problem which is basic to all others, and which has not been given the attention it deserves. My endeavour here will, therefore, be to identify that fundamental problem (Part I ll), and suggest a few grounds for finding a solution to it (Part IV). To begin with, it would serve our purpose better if we go into the origins of the recent changes in the attitude of Christianity towards other religions (Part I), because that will bring into focus the problems the changed attitude of Christianity has generated.